The Effects of Indonesia’s Country-by-Country Reporting Regulation on Multinational Enterprises’ Real Investment - Apryogi Hardoko (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2026)
Does tax transparency discourage investment? Indonesia’s adoption of Base Erosion and Profit Shifting (BEPS) Action 13 concerning Country-by-Country (CbC) Reporting may have an unintended consequence on multinational enterprises’ (MNEs) real investment in Indonesia. If MNE real investment has declined since the introduction of the CbC reporting regulation, the disadvantages of this policy may likely offset its benefits. This paper uses a regression discontinuity design and a difference in differences analysis, employing unique panel data from the Orbis database covering 622 enterprises in Indonesia from 2013 to 2021, to investigate whether MNEs reduced their real investment following the implementation of the CbC reporting regulation. This paper finds that real investment in the treatment group increased after the implementation of the CbC reporting regulation. The unintended consequence of the CbC reporting regulation is likely to discourage MNEs’ real investment in Indonesia. Considering this result, Indonesian tax authorities should implement appropriate policy initiatives to effectively address this issue.